THE EFFECT OF MEDIATION ON CAPITAL FLOWS AND INVESTMENTS ECONOMIC GROWTH IN INDONESIA - Devita Giscka Rezqi Aulia; Hamid Paddu; Indraswati Tri Abdi Reviane (Jurnal Ekonomi, 2022)
This study aims to analyze more about the mediating effect of capital flows on interest rates, inflation rates, and the rupiah exchange rate on economic growth, both directly and indirectly through investment. This research uses time – series secondary data for the period 1992 – 2021. The analytical method used is the structural equations method. The results show that the mediating effect of capital inflows on interest rates has a negative effect on economic growth both directly and indirectly through investment. The mediating effect of capital inflows on inflation rate has a negative effect on economic growth both directly and indirectly through investment. The mediating effect of capital inflows on the exchange rate of the rupiah has a positive effect on economic growth both directly and indirectly through investment. The mediating effect of capital outflows on interest rates has a positive effect on economic growth both directly and indirectly through investment. The mediating effect of capital outflows on inflation rate has a positive effect on economic growth both directly and indirectly through investment. The mediating effect of capital outflows on the exchange rate of the rupiah has a negative effect on economic growth both directly and indirectly through investment.